Otfrid Foerster (1873–1941)—Self-Taught Neurosurgeon and Innovator of Reconstructive Peripheral Nerve Surgery - Gohritz, Andreas; Dellon, Lee A.; Guggenheim, Merlin; Spies, Marcus; Steiert, Andreas; Vogt, Peter M. (Journal of Reconstructive Microsurgery, 2013)
Otfrid Foerster (1873–1941) became a self-taught neurosurgeon during and after WW I, playing a critical role in the development of peripheral nerve reconstruction. Although best known for describing dermatomes, he published over 300 articles on the nervous system. Confronted by thousands of nerve injuries during WW I, as well as poor results and disinterest from his surgical colleagues, Foerster began performing neurolysis and tension-free nerve repairs himself under emergency conditions. He pioneered grafting motor nerve defects by expendable cutaneous nerves (e.g., sural) and performed intraplexal neurotizations and various nerve transfers, such as the pectoral, subscapular, long thoracic, and thoracodorsal nerves in brachial plexus injuries. Foerster championed rehabilitation, recognizing the potential of electrostimulation and physiotherapy to influence cortical reorganization (brain plasticity) and improve recovery after nerve injury. Foerster died from tuberculosis in 1941, leaving a rich reconstructive peripheral nerve legacy; his innovative and visionary spirit serves as a role model.
Keywords: Otfrid Foerster; peripheral nerve; nerve graft; neurolysis; nerve repair